2016
DOI: 10.1002/hup.2527
|View full text |Cite
|
Sign up to set email alerts
|

Association study of polymorphism in the serotonin transporter gene promoter, methylation profiles, and expression in patients with major depressive disorder

Abstract: The serotonin transporter (5HTT) may be associated with the pathogenesis of major depressive disorder (MDD). The 5HTT-linked polymorphic region (5HTTLPR) genotype may determine how levels of 5HTT mRNA are influenced by promoter methylation. We examined the association of 5HTT gene methylation, which influences gene expression, and the 5HTTLPR genotype before antidepressant treatment and expression before and after treatment. The aims of this study were (1) to investigate the association between 5HTT methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Several studies support our findings, reporting no association between SLC6A4 methylation in blood and depression in adults, in either Caucasian [12] or three Asian ( n  = 108; n  = 286; n  = 100) [14, 15, 17] populations, as well as in buccal mucosa from Caucasian adolescents ( n  = 150) [16] and EBV-transformed lymphoblasts ( n  = 192) [18]. In contrast, three studies found positive associations between peripheral SLC6A4 methylation in blood and depression in Caucasian ( n  = 57) [13] and Asian adults ( n  = 151; n  = 84) [19, 20], two of which had overlapping assay regions with our study [19, 20]. Interestingly, Shi et al (2016) found significantly highermethylation at two CpG sites (∆ = 2.52 and 0.15) corresponding to CpG 25.26 in our study, which we failed to find, despite this unit having the highest level and variability of methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support our findings, reporting no association between SLC6A4 methylation in blood and depression in adults, in either Caucasian [12] or three Asian ( n  = 108; n  = 286; n  = 100) [14, 15, 17] populations, as well as in buccal mucosa from Caucasian adolescents ( n  = 150) [16] and EBV-transformed lymphoblasts ( n  = 192) [18]. In contrast, three studies found positive associations between peripheral SLC6A4 methylation in blood and depression in Caucasian ( n  = 57) [13] and Asian adults ( n  = 151; n  = 84) [19, 20], two of which had overlapping assay regions with our study [19, 20]. Interestingly, Shi et al (2016) found significantly highermethylation at two CpG sites (∆ = 2.52 and 0.15) corresponding to CpG 25.26 in our study, which we failed to find, despite this unit having the highest level and variability of methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Okada and colleagues found higher SLC6A4 methylation at a specific CpG site to be positively correlated to the improvement ratio; interestingly, methylation at this particular CpG site was inversely correlated to early trauma in the study (Okada et al, 2014). Nevertheless, Kang et al found less Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A) and Social and Occupational Functional Assessment Scale (SOFAS) improvement to be related to higher methylation ; furthermore, Iga et al reported higher CpG-specific methylation to be associated with less improvement in depressive symptoms as measured by the HAM-D scale (Iga et al, 2016).…”
Section: The Role Of Slc6a4 Methylation In Pharmacological and Psychomentioning
confidence: 91%
“…Notably, both Wankerl et al and Iga et al did find an association between CpG-specific methylation and mRNA expression in peripheral blood suggesting that correlations between methylation and expression cannot be obtained from average methylation percentages but can from CpG-specific analysis. Notably, Iga et al found this association in patients but not in controls (Iga et al, 2016).…”
Section: Methylation and Expressionmentioning
confidence: 94%
See 2 more Smart Citations